2021
DOI: 10.1039/d1cc02396a
|View full text |Cite
|
Sign up to set email alerts
|

A star-shaped cyclopentadithiophene-based dopant-free hole-transport material for high-performance perovskite solar cells

Abstract: A new cyclopentadithiophene (CPDT)-based organic small molecule serves as an efficient dopant-free hole transporting material (HTM) for perovskite solar cells (PSCs). Upon incorporation of two carbazole groups, the resulting CPDT-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The highest occupied molecular orbitals (HOMOs) of these three HTMs are nearly delocalized on the whole molecular skeleton, whereas the lowest unoccupied molecular orbitals (LUMOs) are converging toward the core building block, especially on the fluorine-substituted benzene ring. It is reported that spatially separated HOMO and LUMO levels are in favor of hole extraction and transport . The electrostatic surface potential (ESP) results of these three HTMs demonstrate that the different fluorine substitutions show a negligible effect on the surface potential of peripheral 4,4′-dimethoxy triphenylamine groups, while with the increasing number of fluorine, the electronegativity of the fluorine-substituted benzene ring gradually increases, making the buried surface defect passivation possible through Pb···F action.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The highest occupied molecular orbitals (HOMOs) of these three HTMs are nearly delocalized on the whole molecular skeleton, whereas the lowest unoccupied molecular orbitals (LUMOs) are converging toward the core building block, especially on the fluorine-substituted benzene ring. It is reported that spatially separated HOMO and LUMO levels are in favor of hole extraction and transport . The electrostatic surface potential (ESP) results of these three HTMs demonstrate that the different fluorine substitutions show a negligible effect on the surface potential of peripheral 4,4′-dimethoxy triphenylamine groups, while with the increasing number of fluorine, the electronegativity of the fluorine-substituted benzene ring gradually increases, making the buried surface defect passivation possible through Pb···F action.…”
Section: Resultsmentioning
confidence: 94%
“…It is reported that spatially separated HOMO and LUMO levels are in favor of hole extraction and transport. 31 The electrostatic surface potential (ESP) results of these three HTMs demonstrate that the different fluorine substitutions show a negligible effect on the surface potential of peripheral 4,4′- Figure 2a shows the UV−vis absorption of 2FPPY, 4FPPY, and 6FPPY in THF solution, and the corresponding data is summarized in Table 1. Different fluorine substitutions hardly influence the absorption properties of HTMs.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…75–77 Lin and co-authors reported two novel star-shaped small molecule HTMs, denoted as T-CPDT and C-CPDT, based on a central cyclopenta[2,1- b :3,4- b ′]dithiophene (CPDT) core as its large π-conjugation rigid structure benefits charge transport. 78 The mesoporous n–i–p device fabricated using C-CPDT as HTM without any dopants achieved an excellent PCE of 19.6%, which is significantly higher than that of the device based on T-CPDT (PCE = 11.4%). This is attributed to its enhanced hole transportation ability caused by introducing the planar carbazole group.…”
Section: Perovskite Materialsmentioning
confidence: 88%
“…Here, we have ignored the effect of λext because of its minor role in managing the outer atmosphere of the molecule. These calculations have been done using equations, that is, Equations (1) and (2), 11‐15,17‐19,21‐30 normalλelectron=E0normalE+[E0normalE0] normalλhole=E0+normalE++[E+0normalE0] where, E 0 , E +/− , E 0 +/− and E +/− 0 shows the energy at neutral state, cation/anion state, excited and ground‐state, then neutral at excited‐sate, correspondingly.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Because of their exceptional chemical architecture, these materials are considered to have characteristics of both small organic molecules and polymer materials, such as occupying better solubility and film formation properties, improving thermal stability, and merging distinct structures and physical characteristics 1,2,9 . These molecules have been widely used in organic light‐emitting diodes (OLED), organic field effect transistors (OFET), OSCs, and PSCs 14,15 . Therefore, researchers are interested in synthesizing efficient HTM molecules containing heteroatoms with fused aromatic rings due to their rigidity, coplanarity, and maximum overlap of π‐orbitals for face‐to‐face π‐stacking favoring intermolecular charge transport 16.…”
Section: Introductionmentioning
confidence: 99%